Sex and plumage-type ratios of the Lesser Magellan Goose in southern Chile - Siegfried, W R; Hockey, P A R; Ryan, P G; Bosman, A L (Wildfowl, 1988)
Sex ratios in sheldgeese, especially the Lesser Magellan Goose Chloephaga p. picta were determined from roadside counts over 800 km in southern Chile and on Tierra del Fuego. They were close to parity. Males with white underparts predominated in the north and those with barred underparts in the south. There may also be a north/south cline in the greyish-headed females versus those with reddish heads. The interactions with other species of sheldgeese and with cattle and sheep are discussed.